Optical properties of silicon oxynitride films grown by plasma-enhanced chemical vapor deposition - Aschwanden, R.; Köthemann, R.; Albert, M.; Golla, C.; Meier, Cedrik (Thin Solid Films)
In this paper, silicon oxynitride films (SiON) grown by plasma-enhanced chemical vapor deposition are investigated. As precursor gases silane (SiH4), nitrous oxide (N2O), nitrogen (N2) and ammonia (NH3) are used with different compositions. We find that for achieving high nitrogen content adding ammonia to the precursor mix is most efficient. Moreover, we investigate the balance between adsorption and desorption processes during film growth by investigating the film growth rate as a function of the substrate temperature. From these data we are able to determine an effective activation energy for the film growth, corresponding to the difference between adsorption and desorption energy. Finally, we have thoroughly investigated the optical properties of the films using spectroscopic ellipsometry. From these measurements, we suggest a parametrized model for the refractive index and extinction coefficient in a wide range of compositions based on a Cauchy- and a Lorentz-fit.

Reducing the Schottky barrier height at the MoSe2/Mo(110) interface in thin-film solar cells: Insights from first-principles calculations - Mirhosseini, Hossein; Kiss, Janos; Roma, Guido; Felser, Claudia (Thin Solid Films)

Spectroelectrochemical and morphological studies of the ageing of silver nanoparticles embedded in ultra-thin perfluorinated sputter deposited films - Ebbert, Christoph; Alissawi, N.; Somsen, C.; Eggeler, G.; Strunskus, T.; Faupel, F.; Grundmeier, Guido (Thin Solid Films)

Lift-off of mesoporous layers by electrochemical etching on Si (100) substrates with miscut of 6° off towards (111) - Garralaga Rojas, E.; Terheiden, B.; Plagwitz, H.; Hensen, J.; Wiedemeier, V.; Berth, Gerhard; Zrenner, Artur; Brendel, R. (Thin Solid Films)
Uniform mesoporous Si double layers are formed on 4 inch p-type < 100> wafers with an off orientation of 6º towards < 111> by means of electrochemical etching in ethanoic-based HF electrolytes. These substrates are of interest for the epitaxial growth of III–V compound semiconductor stacks on their top for the production of multi-junction solar cells and very thin electronic devices. We demonstrate transfer of porous layers after an annealing process in hydrogen atmosphere. Electron Back-Scatter Diffraction analysis confirms that the substrate orientation is conserved during the etching and annealing steps. Confocal μ-Raman spectroscopy analysis shows a decrease in the Raman signal intensity after etching and a subsequent increase after annealing while no shift is observed. By means of Atomic Force Microscopy, analysis the surface appearance after the etching and annealing steps can be visualized. The mean surface roughness varies during the process from 0.55 nm for the unprocessed wafers to 0.27 nm after etching and 0.78 nm after annealing. The decrease of average roughness after etching is caused by an electropolishing step prior to porous formation. Despite of slight increase of mean surface roughness after annealing the samples are still appropriate for high quality epitaxial growth and subsequent lift-off.
Keywords: Porous Si; Layer transfer; Thin-film; Photovoltaics

Influence of process parameters on the crystallinity, morphology and composition of tungsten oxide-based thin films grown by metalorganic chemical vapor deposition - de los Arcos de Pedro, Maria Teresa; Cwik, Stefan; Milanov, Andrian P.; Gwildies, Vanessa; Parala, Harish; Wagner, Tristan; Birkner, Alexander; Rogalla, Detlef; Becker, Hans-Werner; Winter, Jörg; Ludwig, Alfred; Fischer, Roland A.; et al. (Thin Solid Films)

X-ray photoelectron spectroscopy on implanted argon as a tool to follow local structural changes in thin films - Lahrood, Atena Rastgoo; de los Arcos de Pedro, Maria Teresa; Prenzel, Marina; von Keudell, Achim; Winter, Jörg (Thin Solid Films)

X-ray absorption near-edge spectroscopy investigation of the oxidation state of Pd species in nanoporous SnO2 gas sensors for methane detection - Wagner, T.; Bauer, M.; Sauerwald, T.; Kohl, C.-D.; Tiemann, Michael (Thin Solid Films)
We report the correlation of the aging of Pd-doped SnO2 methane sensors with the change of the oxidation state of Pd. Mesoporous SnO2 doped with palladium species was prepared and exposed to different gas mixtures at high temperature (600 °C) to simulate long term usage. After each exposure step a fraction of the sample was cooled down to “freeze” the current oxidation state of Pd which was then analyzed by X-ray Absorption Near-Edge Spectroscopy (XANES) using the 'white line' (i.e. the absorption peak corresponding to the transition from the 2p3/2 core level to unoccupied 4 d states) intensity of the L(III) edge as a probe for the oxidation state. The Pd oxidation state correlates with the response of the resistive SnO2 sensor to methane gas, as determined by measuring the gas response to different concentrations of methane. Samples treated with 5000 ppm methane in air show a significant reduction of Pd(II) to Pd(0), depending clearly on the carrier gas (synthetic air, pure nitrogen) and on the temperature (600 °C vs. 300 °C).

Photocatalytic ozone sensor based on mesoporous indium oxide: Influence of the relative humidity on the sensing performance - Wagner, T.; Hennemann, J.; Kohl, C.-D.; Tiemann, Michael (Thin Solid Films)
Mesoporous In2O3, synthesized by a nanocasting procedure, is used as a resistive gas sensor for ozone in very low concentrations (from 20 ppb to 2.4 ppm) at room temperature. Its sensing performance is substantially increased by illumination with blue light (460 nm, 2.7 eV). For low ozone concentrations the sensor response increases with increasing humidity. However, higher humidity also results in the occurrence of a saturation of the response at lower ozone concentrations; this is rationalized by assuming a poisoning of surface active sites by hydroxyl groups.

Gas sensor based on ordered mesoporous In2O3 - Wagner, T.; Sauerwald, T.; Kohl, C.-D.; Waitz, T.; Weidmann, C.; Tiemann, Michael (Thin Solid Films)
We present the preparation of a semiconductor gas sensor based on ordered mesoporous In2O3. The In2O3 was synthesized by structure replication procedure from cubic KIT-6 silica. A detailed analysis of the morphology of the mesoporous powders as well as of the prepared sensing layer will be shown. Unique properties arise from the synthesis method of structure replication such as well defined porosity in the mesoporous regime and nanocrystallites with high thermal stability up to 450 °C. These properties are useful for the application in semiconducting gas sensors. Test measurements show sensitivity to methane gas in concentrations relevant for explosion prevention.

Ordered mesoporous ZnO for gas sensing - Wagner, T.; Waitz, T.; Roggenbuck, J.; Fröba, M.; Kohl, C.-D.; Tiemann, Michael (Thin Solid Films)
We report on the synthesis and the gas-sensing properties (CO and NO2 detection) of mesoporous zinc oxide. A two-step structure replication method for the synthesis is employed. In the first step mesoporous SBA-15 silica is prepared by the utilization of self-organization of amphiphilic organic agents. This mesoporous silica is used as the structure matrix for synthesizing mesoporous carbon CMK-3, which, in turn, is employed for yet another replication step, using zinc nitrate as the precursor. The resulting material is characterized by X-ray diffraction and nitrogen physisorption and its gas-sensing properties are compared with a non-porous ZnO sample.